Assessment of a pharmacovigilance module: An interventional study on knowledge, attitude, and practice of pharmacy students - Subish Palaian; Mohamed Izham Mohamed Ibrahim; Pranaya Mishra; Pathiyil Ravi Shankar (Wolters Kluwer Medknow Publications, 2021)
Background: The aim of the study was to assess the impact of a pharmacovigilance module on the knowledge, attitude, and practice (KAP) of pharmacy students and elucidate their feedback on the module. Methodology: Bachelor of pharmacy students at Pokhara University, Nepal, were assessed for their baseline KAP on drug safety and related issues using a KAP questionnaire (Cronbach alpha 0.70) consisting of 25 questions. Students' baseline KAP was assessed and after that, they were grouped into either control (2nd and 4th year) or test (1st and 3rd year) groups. The later received the pharmacovigilance training in three 1-h sessions spread over 6 months at 0, 90, and 180 days; the sessions covered introduction to pharmacovigilance, theoretical aspects of pharmacovigilance, and adverse drug reaction reporting procedures. KAP scores and student feedback were analyzed at 5% significance level. Results: A total of 124 students (control = 56 and test = 68) were studied. The median (interquartile ranges [IQRs]) of the baseline scores prior to grouping the students into control and test groups was 20 (18.25-21.00) for knowledge, 19.5 (18.00-21.00) for attitude/practice, and 39 (37.00-41.00) for the total score. Males (n = 81) had a slightly higher median score of 40 (37-42) than females (n = 43), who had a median score of 38 (36-41). The KAP score for the control group was 40 (38-42) at baseline, 42 (20-44) during first follow-up, 41.5 (40-44) during second follow-up, and 41 (39-44.5) during third follow-up. For the test group, upon intervention, the KAP scores improved from 39 (36.25-40.75) at baseline to 42 (39.50-44.00) at the 1st follow-up, 43 (41-45) at the 2nd follow-up, and 44 (42-45) at the 3rd follow-up (P < 0.001). The median feedback score (IQR) was 86 (81.5-90.0). Conclusions: Pharmacy students had good attitude/practice scores and relatively poor knowledge scores at baseline, which improved postintervention. Student feedback about the module was positive.